Indonesia's Capital Market Reaction During The Covid-19 Pandemic at Manufacturing Companies Listed On The Indonesia Stock Exchange - Khairul Azwar; Elly Susanti; Juan Anastasia Putri (Jurnal Akuntansi dan Pajak, 2022)
On March 2, 2020 until April 30, 2020 positive cases of Covid-19 are increasing and widespread in various provinces in Indonesia. This will affect the performance of the Indonesian stock market. This condition was seen on March 2, 2020 and April 17, 2020 where the JCI (Jakarta Composite Index) touched a low of 3,937 while the average daily stock transaction volume fell by 51.87% from the beginning of 2020. This study aims to determine the difference between Abnormal Return (AR) and Trading Volume Activity (TVA) before and after the Covid-19 pandemic in manufacturing companies listed on the Indonesia Stock Exchange. This study was conducted at a manufacturing company listed on the Indonesia Stock Exchange in BEI with 98 with a research time of 21 days (March 26, 2020 – April 24, 2020). Data analysis in this study uses different test paired sample t-test, with the study's results showing an insignificant difference in abnormal return before and after the announcement of PSBB I (Large-Scale-Social Restrictions I). At the same time, there are significant differences before and after the announcement of PSBB I for trading volume activity. The results of this study can have implications for investors and potential investors as a source of information in decision making when investing and as a guideline to conduct an analysis of capital market performance as a basis for choosing companies that can provide large returns when important events such as the Covid-19 case occur.